The Influence of Healthcare Professionals’ Clothing Color on Patients’ Perceptions: A Narrative Review - Czerepak, Gabriela; Jędras, Aleksandra; Bednarz, Katarzyna; Pociask, Weronika; Pondo, Wojciech; Gliwa, Katarzyna; Pest, Jakub; Czajkowska, Weronika; Zowczak, Wiktoria; Barszcz, Aleksandra (Quality in Sport, 2026)
Modern medicine increasingly relies on a partnership model in which the patient’s trust in medical staff plays a key role. When assessing the competence, credibility, and empathy of physicians, patients rely not only on clinical information but also on nonverbal cues, such as appearance and attire. The aim of this study was to compile and analyze current knowledge regarding the impact of medical attire—its color and style—on patients’ perceptions of medical staff. This study is a narrative literature review utilizing the PubMed and ScienceDirect databases. The analysis included publications from 2016 to 2025 concerning the impact of the color and type of medical attire on patients’ perceptions of medical staff. The search strategy included combinations of keywords related to medical attire, clothing color, patient trust, fear of the dentist (dentophobia), and the doctor-patient relationship. After selecting the publications, nine studies were included in the analysis. The analyzed studies showed that the color of medical attire influences the assessment of medical staff’s professionalism, competence, empathy, and credibility. Shades of blue and navy blue were rated most positively, as they were associated with professionalism, calmness, and a high level of competence. The color black was consistently rated negatively and associated with lower levels of trust and empathy. Green uniforms were strongly associated with procedural specialties, particularly surgery, but did not always receive the highest ratings in terms of interpersonal traits. In many studies, the white coat remained a significant symbol of professionalism, especially among older patients and in outpatient care. The results indicate that the color of medical attire is a significant element of nonverbal communication and influences how patients perceive medical staff, enhances patient comfort, and builds trust in the patient-physician relationship.